Thyroid Hormone Status in Severely Malnourished Children between 6 Months to 5 Years Admitted to Nutritional Rehabilitation Centre of a Tertiary Care Hospital (International Journal of Child Health and Nutrition, 2023)
Introduction: Severe malnutrition poses a significant risk to the thyroid gland's function and hormonal balance, which can lead to numerous physiological and developmental complications. Understanding the relationship between severe malnutrition and thyroid hormone status is crucial for the effective management of these children.Aim and Objective: To investigate the prevalence and patterns of thyroid hormone abnormalities in severely malnourished patients with subgroup analysis in Marasmus, Kwashiorkor, and edematous malnourished patients.Methodology: We conducted a cross-sectional study involving 116 children diagnosed with severe acute malnutrition (SAM). The study protocol was approved by the Institution Ethics Committee. Well-informed written consent in the local language was taken from parents. SAM was diagnosed and managed according to WHO criteria (1). Comprehensive laboratory investigations were conducted to assess serum levels of thyroid-stimulating hormone (TSH), free thyroxine (T4), and triiodothyronine (T3). Statistical analysis was performed to examine the associations between these variables and SAM.Results: Most of the 116 subjects included in the study were male (53.4%) and had a lower socioeconomic status (43.9%). The age distribution of the children aged below 5 years revealed that 46.5% were between 12 and 36 months old. In the present study, Marasmus was 55.2%, Kwashiorkor was 12.1%, and edematous malnutrition was 32.7%. Among 116 participants, 94.8% were discharged, while 5.2% were expired during treatment. The mean levels of fT3, fT4, and TSH were 1.88±1.06 pg/ml, 0.99±0.84 ng/dl, and 3.22±0.87 µIU/ml, respectively. Most SAM patients had low fT3, fT4, and TSH levels relative to the normal range.Conclusion: Monitoring of thyroid hormone status in SAM patients is mandatory for this vulnerable population.